Gratitude to God Predicts Religious Well-Being over Time - Philip Watkins; Michael Frederick; Don E. Davis (Religions, 2022)
The authors used a prospective design to investigate how gratitude to God predicts religious well-being over time. Gratitude to God is a central aspect of monotheistic religions, and thus may be particularly important to the religious/spiritual well-being of believers. Participants completed online measures of trait and state gratitude to God, along with spiritual well-being, nearness to God, and religious commitment scales over a one-to-two-month period. General well-being, trait gratitude, and the Big Five personality traits were also assessed. After controlling baseline levels, trait gratitude and the Big Five personality traits, dispositional gratitude to God at Time 1 predicted increased religious well-being, nearness to God, and religious commitment at Time 2. Although gratitude to God was significantly related to general well-being variables in cross-sectional analyses, it did not predict these variables over time. Validity data for the gratitude to God measures are also presented. The results suggest that gratitude to God is important to religious/spiritual well-being, and gratitude to God may be a critical variable for research on positive psychology and the psychology of religion/spirituality.